2014
DOI: 10.1186/preaccept-4848873741397798
|View full text |Cite
|
Sign up to set email alerts
|

ß-amyloid induces a dying-back process and remote trans-synaptic alterations in a microfluidic-based reconstructed neuronal network

Abstract: Introduction: Recent histopathological studies have shown that neurodegenerative processes in Alzheimer's and Parkinson's Disease develop along neuronal networks and that hallmarks could propagate trans-synaptically through neuronal pathways. The underlying molecular mechanisms are still unknown, and investigations have been impeded by the complexity of brain connectivity and the need for experimental models allowing a fine manipulation of the local microenvironment at the subcellular level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 12 publications
2
17
0
Order By: Relevance
“…A surprising observation was that upon axonal rotenone insults in low glucose conditions, although the treated axonal segments degenerate through a caspase-dependent pathway13, no significant retrograde spreading toward the cell body was evidenced in basal conditions. Interestingly, while our previous observations suggested that axons have high intrinsic resistance toward direct apoptosis activation1365, a recent report showed that direct axonal apoptotic degeneration is gated by a somatic apoptotic signaling19. Collectively these findings support the notion that unchallenged parts of the neurons may buffer the spreading of toxic signals in the cytoplasm as previously hypothesized66 and suggested by experimental results showing that locally induced mitochondrial damages in vivo are due to a local and reversible process39.…”
Section: Discussionsupporting
confidence: 78%
“…A surprising observation was that upon axonal rotenone insults in low glucose conditions, although the treated axonal segments degenerate through a caspase-dependent pathway13, no significant retrograde spreading toward the cell body was evidenced in basal conditions. Interestingly, while our previous observations suggested that axons have high intrinsic resistance toward direct apoptosis activation1365, a recent report showed that direct axonal apoptotic degeneration is gated by a somatic apoptotic signaling19. Collectively these findings support the notion that unchallenged parts of the neurons may buffer the spreading of toxic signals in the cytoplasm as previously hypothesized66 and suggested by experimental results showing that locally induced mitochondrial damages in vivo are due to a local and reversible process39.…”
Section: Discussionsupporting
confidence: 78%
“…Axonal degeneration following neuronal insults, such as toxins, metabolic disturbances, infections and mutations growth, occurs in a process called ‘dying-back’ that starts distally and then spreads toward the cell body; 30 this phenomenon was also found in neurodegenerative diseases including Alzheimer’s and Parkinson’s diseases over weeks or months. 31, 32 Although there is no report establishing that dendrite degeneration occurs by a dying-back process, the present study provides a clue that chronic brain ischemia may induce a dying-back process of dendrite degeneration. However, more evidence is needed to clarify this process as well as the potential molecular mechanism.…”
Section: Discussionmentioning
confidence: 57%
“…To extend our study to mature neurons, we combined the use of primary cultures of mouse cerebellar granule neurons (CGNs) and of a reconstructed cortico-striatal neuronal network grown on microfluidic chips [ 34 36 ]. CGNs are helpful to probe the effect of prion infection on the axon and dendrites [ 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%